Long-term outcomes of clinical and pathological-staged T3 N3 esophageal cancer. Issue 8 (16th January 2020) - Kamarajah, S K; Newton, N; Navidi, M; Wahed, S; Immanuel, A; Hayes, N; Griffin, S M; Phillips, A W
Summary: Locally advanced esophageal cancer is associated with poor long-term survival. Pre- and post-treatment stages may differ because of neoadjuvant therapy and inaccuracies in staging. The aim of this study was to determine the outcomes of patients staged with clinical T3 N3 and pathological T3 N3 carcinoma of the esophagus and determine differences between the groups. Consecutive patients from a single unit between 2010 and 2018 were included with either clinical (cT3 N3) or pathological (pT3 N3) esophageal cancer. Outcomes were compared between patients that underwent esophagectomy with or without neoadjuvant treatment and those patients staged cT3 N3 treated non-surgically (NSR). Patients were staged using the TNM 8. This study included 156 patients, 63 patients were staged cT3 N3 initially and had NSR treatment, only three of these had radical treatment. Of the remaining 93 patients who underwent esophagectomy, 34 were initially staged as cT3 N3, 54 were found to be pT3 N3 having been staged earlier initially, and five were unchanged before and after treatment. Median overall survival (OS) for surgical cT3 N3 patients was significantly longer than pT3 N3 and NSR (median: NR vs 19 vs 8 months, P  < 0.001). Twenty-seven patients with cT3 N3 had lower staging following treatment, while three had a higher stage. T3 N3 disease carries a poor prognosis. Within this cohort, cT3 N3 disease treated surgically has a high 5-year OS suggesting possible over-staging and stage migration due to neoadjuvant therapy. Those not having surgery, have a dismal prognosis. The impact of neoadjuvant treatment cannot be predicted and, current staging modalities may be inaccurate. Clinical stage should be used with caution when counseling patients regarding management and prognosis.